Fast solid‐state on‐load tap change using two current‐controlled voltage‐source inverters. Issue 10 (1st October 2014) - Ekström, Rickard; Thomas, Karin; Leijon, Mats
Abstract : A new topology for on‐load tap change using two current‐controlled voltage‐source inverters is demonstrated. With this topology, no additional tap change circuitry is required. This configuration can be useful when optimising the power extraction from renewable energy sources, and may replace a DC/DC converter. It is possible to run the inverters in parallel for higher current capacity, or run them in series across the transformer to improve the harmonic output. The topology can be extended to any number of taps, adding one mechanical contactor per tap. The procedure for the tap change, including the control implementations to keep active and reactive grid power flows constant throughout the tap change, is described. Experimental results are presented to show the viability of the proposed topology. Tap changes are conducted on all phases simultaneously, and individually at each phase current zero‐crossing. Variations in grid power are investigated for the two strategies. Also, a dead‐time in the tap change is introduced to evaluate how control system delays will appear as grid power dips.